2021
DOI: 10.7774/cevr.2021.10.2.198
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of shingles after COVID-19 vaccine: is it a possible adverse effect?

Abstract: Coronavirus disease 2019 (COVID-19) exhibit mild to moderate symptoms, whereas 15% of COVID-19 cases progress to pneumonia, some associated cutaneous findings are also reported as maculopapular eruptions, morbilliform rashes, urticaria, chickenpox-like lesions, and livedo reticularis. The inactivated COVID-19 vaccines are authorized for use in some countries including Turkey. Here, we report an unusual case of varicella-zoster virus (VZV) reactivation in a 68-year-old male patient who was vaccinated against CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 17 publications
1
36
1
Order By: Relevance
“…The search yielded a total of 54 patients consisting of 27 male and 27 females. Cases were reported worldwide including USA, 10 , 11 Lebanon, 12 Turkey, 13 , 14 , 15 Greece, 16 Italy, 17 India, 18 Israel, 19 Finland, 20 Taiwan, 21 Spain, 22 and Portugal. 23 There were cases with known risk factors for herpes zoster, which included age more than 50 years ( n = 36), immunological disorders ( n = 10), chronic disease ( n = 25), metabolic disorder ( n = 13), malignancy ( n = 4), and psychiatric disorder ( n = 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search yielded a total of 54 patients consisting of 27 male and 27 females. Cases were reported worldwide including USA, 10 , 11 Lebanon, 12 Turkey, 13 , 14 , 15 Greece, 16 Italy, 17 India, 18 Israel, 19 Finland, 20 Taiwan, 21 Spain, 22 and Portugal. 23 There were cases with known risk factors for herpes zoster, which included age more than 50 years ( n = 36), immunological disorders ( n = 10), chronic disease ( n = 25), metabolic disorder ( n = 13), malignancy ( n = 4), and psychiatric disorder ( n = 2).…”
Section: Resultsmentioning
confidence: 99%
“…9 , 10 Toll‐like receptors (TLR) stimulation of innate immunity might be the connection between COVID‐19 vaccine and HZ development. 15 The stimulation of these receptors has been related to the reactivation of VZV, allowing the latent virus to remain dormant in the afflicted people. 14 The COVID‐19 immunization may lead to the production of type I IFNs and other inflammatory cytokines, activating T‐ and B‐cell immunity and negatively affecting antigen expression, resulting in herpes zoster reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…In this review, we found that the reactivation of VZV following the COVID‐19 vaccines has been reported all over the world and with different types of vaccines. Reactivation of VZV following the vaccination using inactivated COVID‐19 has only been reported in India and Turkey (Aksu & Öztürk, 2021 ; Arora et al, 2021 ; Bostan & Yalici‐Armagan, 2021 ; Özdemir et al, 2021 ). The affected age had a wide range (21–94 year old) with a mean of 58.9 years.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible mechanism may be local immunity impairment by direct trauma and subsequent immune escape of latent virus [10]. Reactivations of VZV after different types of vaccines (vaccine against influenza, hepatitis A, rabies, Japanese encephalitis, and COVID-19) were described in adult patients [12,13,14], but to the best of our knowledge HZ after hepatitis B vaccine was not reported yet. Immunomodulation after hepatitis B vaccine was observed [15], but there is weak evidence that hepatitis B vaccine contributed to VZV reactivation in our case.…”
Section: Discussionmentioning
confidence: 91%